If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(x+1)=x-8+2(6x+3)
We move all terms to the left:
-5(x+1)-(x-8+2(6x+3))=0
We multiply parentheses
-5x-(x-8+2(6x+3))-5=0
We calculate terms in parentheses: -(x-8+2(6x+3)), so:We get rid of parentheses
x-8+2(6x+3)
determiningTheFunctionDomain x+2(6x+3)-8
We multiply parentheses
x+12x+6-8
We add all the numbers together, and all the variables
13x-2
Back to the equation:
-(13x-2)
-5x-13x+2-5=0
We add all the numbers together, and all the variables
-18x-3=0
We move all terms containing x to the left, all other terms to the right
-18x=3
x=3/-18
x=-1/6
| 4=2r-2 | | 27=x/8+3 | | 8x-3x+7=2x+3x+11- | | 145-w=218 | | c/2=9=12 | | -8-2c=-16 | | 5x^2-16x=5 | | 6–13=(x+4)11 | | 14-35x=14-3x | | 3x-10(x+2)=13×13-7x | | -6=c/2-9 | | 30=5(c+1) | | 11(t)=-20+11t | | x2+5x-3x=0 | | 3u-18=6(u-2) | | -5=d/2-7 | | 7/5=p+7/4 | | 118+8x+6=180 | | (x)(x)+x-22=0 | | 8^2+16x+9=0 | | 2-2p=12 | | 1/3x+10=3/5x | | 5v=81-4v | | -18=2(u-4)-7u | | 2/8x=1/8x+2 | | 10-x=8x+22 | | 3*x^2-48/(x^2)=0 | | 322=7/10x | | X^2+6x+81=0 | | 2g+15=8g–3 | | 6-7(-3x+6)=18-6x | | x-1+5=4 |